1970
DOI: 10.1038/bjc.1970.49
|View full text |Cite
|
Sign up to set email alerts
|

A Computer-aided Study on the Tissue Changes in Oral Keratoses and Lichen Planus, and an Analysis of Case Groupings by Subjective and Objective Criteria

Abstract: Analysis of the histological findings on an objective basis, using a cluster analysis programme, provided an encouraging degree of separation into the diagnostic groups. When a number of known carcinoma cases were included in the cluster analysis as " markers ", a small number of leukoplakia and keratosis cases were placed by the computer into the same cluster as these " markers ". Of the original 187 cases originally diagnosed as leukoplakia or keratosis, 4.8% are known to have developed a carcinoma, but of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
1

Year Published

1973
1973
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 10 publications
2
43
0
1
Order By: Relevance
“…The material used for the previous studies, and for part of the work described here, consisted of 235 consecutive biopsies of oral lesions on which the final clinicopathological diagnosis was leukoplakia, keratosis or lichen planus (the definitions of the first two of these terms were given in Kramer et al, 1970a). This was a retrospective survey, so that follow-up was available on almost all of the patients.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The material used for the previous studies, and for part of the work described here, consisted of 235 consecutive biopsies of oral lesions on which the final clinicopathological diagnosis was leukoplakia, keratosis or lichen planus (the definitions of the first two of these terms were given in Kramer et al, 1970a). This was a retrospective survey, so that follow-up was available on almost all of the patients.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The definitions of the histological criteria were summarized previously (Kramer et al, 1970a). The observer was trained to record each feature independently, and without any attempt at interpretation.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leukoplakia undergoes carcinomatous transformation in about 5 % of patients (Kramer et al, 1970), and it is the precancerous nature of some of these lesions that makes it an important condition for investigation. An immunopathological investigation of this disease revealed that saline homogenates of leukoplakic tissue induce slight stimulation of autologous lymphocytes (Lehner, 1970a (Lehner, 1971 .…”
mentioning
confidence: 99%